Language policy, homelessness and neoliberal urbanization: The case of San Francisco's Union Square. (11th July 2016) - Wee, Lionel
Abstract : One example of the impact of neoliberalism on urbanization is that of the Business Improvement District (BID), where business and property owners collectively manage a district to ensure that it has an appropriate 'business climate'. The responses of BIDs to the language practices of the homeless, such as panhandling, tend to be ambivalent because homelessness is an issue that requires sensitivity. Nevertheless, overly aggressive panhandling can have adverse repercussions for businesses. This paper focuses on San Francisco's Union Square, which is the city's commercial retail center, and makes two key points. One, language policy needs to be viewed as planned, unplanned or transgressive, where these characterizations are necessarily from the perspective of an specific actor, such as the Union Square BID. Two, there are interesting attempts to transform panhandling practices from above, pushing these towards neoliberalism with the consequence that the panhandlers themselves sometimes respond by reimagining panhandling as work or a business. Abstract : 新自由主义对都市化进程造成冲击的其中一个例子, 是商业区协进会的设立。在此一安排下, 商业与业主共同管理商业区, 一起营造合宜的商业环境。协进会对流浪者例如乞丐的语言习惯的反应经常是含糊不清的, 因为流浪人口问题是一敏感课题, 需要小心处理。无论如何, 过度的行乞行为会影响生意。本文以三藩市的商业零售中心联合广场为研究对象, 提出两点观察:第一, 语言政策可根据特定一方如协进会的立场, 被归类为"有计划"、"无计划"或者"逾越界限"。第二, 我们发现有些自上而下的措施, 试图以值得关注的方式改变行乞的现象, 并把这些行为导向新自由主义。这样的举措会带来如下结果:乞丐们在回应时, 有时候会把行乞重新想象为一份工作或者一门生意。